2021
DOI: 10.1002/14651858.cd013122.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Secondary prevention of variceal bleeding in adults with previous oesophageal variceal bleeding due to decompensated liver cirrhosis: a network meta-analysis

Abstract: Secondary prevention of variceal bleeding in adults with previous oesophageal variceal bleeding due to decompensated liver cirrhosis: a network meta-analysis (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 345 publications
0
9
0
Order By: Relevance
“…It has been shown that approximately 30–40% of liver cirrhosis patients exhibit upper gastrointestinal bleeding as the disease progresses, which is often the most common cause of first hospitalization in patients with advanced cirrhosis [ 22 ]. Also, several studies have reported that EGVB can complicate the outcome in liver cirrhosis patients [ 23 25 ]. These studies have further analyzed the risk factors of bleeding and rebleeding after endoscopic treatment to inhibit the recurrence of EGVB and improve the quality of life of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that approximately 30–40% of liver cirrhosis patients exhibit upper gastrointestinal bleeding as the disease progresses, which is often the most common cause of first hospitalization in patients with advanced cirrhosis [ 22 ]. Also, several studies have reported that EGVB can complicate the outcome in liver cirrhosis patients [ 23 25 ]. These studies have further analyzed the risk factors of bleeding and rebleeding after endoscopic treatment to inhibit the recurrence of EGVB and improve the quality of life of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in mortality between ligation alone and ligation plus NSBBs for prevention of rebleeding. It is difficult to deduce from a recent network meta-analysis (3,526 participants, 48 randomized trials) the effect of NSBBs on survival when compared to other active treatments ( 131 ). It does not appear that there is a major difference.…”
Section: Indications For Nsbbs Results From Randomized Trialsmentioning
confidence: 99%
“…Also, the volume of rebleeding reduced and the therapeutic effect was better ( 13 ). The risk of rebleeding after endoscopy is mainly related to the level of portal hypertension, the severity of varices, and the status of coagulation function in patients ( 32 ). Based on these results, we recommend endoscopic primary prophylaxis for patients with cirrhosis complicated with esophagogastric varices, rather than waiting for emergency treatment after the first episode of variceal bleeding.…”
Section: Discussionmentioning
confidence: 99%